Status Keberdosaan dalam Kerajaan Seribu Tahun menurut Perspektif Pre-Millenialisme - Harry Sudarma (LPPM STT Baptis Kalvari, 2022)
The state of human sinfulness is a topic that will always arise curiosity to be discussed, especially in the millennial or 1000 years timeframe. The end-time discussion about the sinful status of humans certainly cannot be separated from the concept of how humans, in this case believers, can sin. This concept begins with the fall of man in the garden of Eden and continues to the new concept of life presented in the Letter of James. Understanding the trials of both peirasmos and dokimos will help answer the status of human beings in the age of 1000 years of peace with Christ.`